Kritik Arsitektur terhadap Aspek Keselamatan Sarana Penyelamatan Jiwa Bangunan Gedung Studi Kasus: Gedung Pusat Antar Universitas (PAU) ITB Bandung - Muhamad, Yudha Ariep; Ilhamdaniah, Ilhamdaniah; Widaningsih, Lilis (Universitas Batanghari Jambi, 2024)
Safety at the building is a safe condition physically, socially, spiritually, psychologically and other threats that endanger humans. Building Safety not only focus on active fire protection, but also need to concern about passive protection. Regarding from that safety aspect, the aspect of building life saving is a prevention for building users so that they have time for evacuation process until they leave the building. The aspect of saving lives is reviewed from the fulfillment of criteria such as distance between buildings, fire fighting access routes, pavement layers or hardstanding, fire fighting access inside buildings, access to exit facilities (corridors), access to exit facilities (doors), lighting on evacuation routes. , Signage, Placement of assembly point. So that an evacuation plan is created along with the fulfillment of protect users in saving lives at the building.